2007
DOI: 10.1258/135763307781645031
|View full text |Cite
|
Sign up to set email alerts
|

Improved communication between hospital and general practice using online patient discharge summaries

Abstract: We compared the information contained in traditional 'To Take Out (TTO)' discharge prescriptions and dictated letters with the information in discharge summaries from an online system. We also investigated the satisfaction of general practitioners (GPs) with the two types of discharge communication. One group of 30 patients were discharged using traditional TTOs and dictated letters and a second group of 30 patients was discharged using the computer generated summary. The summaries were assessed against the 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 1 publication
1
11
1
Order By: Relevance
“…This result contradicts the findings of other audits, including that by Scullard et al (2007) and Maslove et al (2009).…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…This result contradicts the findings of other audits, including that by Scullard et al (2007) and Maslove et al (2009).…”
Section: Discussioncontrasting
confidence: 97%
“…Each standard was given a score of 0 (absent) or 1 (present). This scoring method is similar to the one used by Scullard et al (2007). For each discharge summary, the sum of the scores of all standards was calculated as the total scores.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The identified study designs consisted of nine retrospective audits:18 19 21 23–26 28 30 six surveys, 17 20 22 23 29 31 one blinded randomised controlled trial (RCT),29 one interrupted time sequence27 and one employing semistructured interviews 18…”
Section: Resultsmentioning
confidence: 99%
“…Computergenerated discharge summaries distributed via an online system may provide a more sustainable solution. Pilot studies of such systems have reported positive results, 7,8 but they still appear a distant prospect for many NHS trusts.…”
Section: Discussionmentioning
confidence: 99%